PENGARUH INFLASI DAN NILAI TUKAR RUPIAH ATAS DOLAR AMERIKA SERIKAT TERHADAP HARGA SAHAM PT KIMIA FARMA TBK - Wildayani "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to examine partially and simultaneously the effect of Inflation and the Rupiah Exchange Rate of the Share Price of PT Kimia Farma. Where the independent variable in this study is Inflation and the Exchange Rate of Rupiah on Dolar AS and the dependent variable is the Stock Price. This study uses secondary data in the form of company financial statements and annual reports annual report of PT Kimia Farma Tbk for the period 2014-2018. Data analysis in this study using simple, multiple linear regression, t-test and f-test, the coefficient of determination by using the SPSS 16 device program. The results of the analysis show that the Inflation variable partially (t test) influences the stock price, the variable exchange rate of the rupiah affects the stock price of PT Kimia Farma Tbk. Simultaneous results (test f) indicate the influence of inflation and the rupiah exchange rate on the stock price of PT Kimia Farma Tbk.Keywords: Inflation, rupiah exchange rate (exchange rate), stock price